Nomenclature issues into southern of South American species of Begonia (Begoniaceae) - Martín, Claudia M.; Ospina, Juan C.; Zanotti, Christian A. (Phytotaxa, 2017)
This paper clarifies the typification of nine species of Begonia from South America. Lectotypes were designated for the names Begonia balansae, B. argentinensis [= B. boliviensis], B. boliviensis var. latipetala, B. subcucullata and B. cucullata var. arenosicola [= B. cucullata], B. fiebrigii, B. micranthera, B. hieronymi [=B. micranthera var. hieronymi] and B. subvillosa. Finally, we propose B. subcucullata and B. cucullata var. arenosicola as a new synonyms under B. cucullata.